Influence Of Engagement, Work Environment, Motivation, Organizational Learning, And Supportive Culture On Job Satisfaction - Muhammad Majid; Mohamad Faizal Ramli; Basri Badyalina; Azreen Roslan; Azreen Jihan Che Mohd Hashim (Macrothink Institute, 2024)
This paper intends to investigate the role of engagement, motivation, work environment, supportive culture, and organizational learning on job satisfaction. Responses were collected from 169 employees in Malaysian higher education sector. Further, the data obtained were analysed by using Statistical Package for the Social Sciences (SPSS). The results indicated that there are positive and significant relationships between engagement, supportive culture, motivation, and work environment on job satisfaction among employees of Malaysian higher education sector. However, organizational learning is not a significant towards job satisfaction. In future research, employees from private universities and public universities can be studied as comparison. By conducting these comparisons, it will help in creating plans to narrow down the gaps between these two sectors. In addition, the results will help to enhance the rising literature on job satisfaction from Asian context as this study was based on Malaysian samples. Data from employees working in different higher education institutions was utilized for this study to ensure the unbiased responses. Therefore, this study contributes to the literature concerning job satisfaction among employees, and the results of this study provide significant evidence on the influence of engagement, motivation, work-environment, organizational learning and supportive culture on job satisfaction in Malaysian higher education sector.